2015
DOI: 10.3126/on.v12i1.12251
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of Carp testis as an alternative to 17 α-Methyltestosterone on Tilapia sex reversal

Abstract: 17 α-Methyltestosterone (MT) is a commonly used synthetic androgen for the all male tilapia fry production. The probable residual effect of MT on human health and environment has been a concern. Two trials for two seasons were conducted to evaluate the effectiveness of carp testis (CT), as a source of natural androgen, on sex reversal of Nile tilapia (Oreochromis niloticus) and compare it with MT at Department of Aquaculture, Agriculture and Forestry University, Nepal, using completely randomised block deign (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…It was perceived during experimental trial that longer the immersion time, more survival threats would be there for hatchlings. Hence, greater chances of survival are expected with control group while group of fingerlings confronting the hormones (either through feeding or via immersion time), however drive an opposed conclusion as Khanal et al(2014) reported.…”
Section: Hatching Percentage and Survivalmentioning
confidence: 72%
See 1 more Smart Citation
“…It was perceived during experimental trial that longer the immersion time, more survival threats would be there for hatchlings. Hence, greater chances of survival are expected with control group while group of fingerlings confronting the hormones (either through feeding or via immersion time), however drive an opposed conclusion as Khanal et al(2014) reported.…”
Section: Hatching Percentage and Survivalmentioning
confidence: 72%
“…By utilizing egg immersion technique, commercially beneficial results in various fish species have been obtained. Groups confronting the hormones (through immersion times) produced pronounced gain in maleness percent as found in work of Khanal et al (2014).…”
Section: Sex Reversal Percentmentioning
confidence: 90%
“…[23] used a dose rate of 75mg 17α-MT in feed and recorded a maximum O. mossambicus male production of 98.09% [33]. Administration of 17α-MT effectively masculinized Rhamdia quelen fry; however, the lowest dose of 60 mg/kg of feed is recommended, since higher doses have inhibitory effects on gonadal development in both sexes [20] found that Labeo rohita testis produced more male population and can safely and effectively replace the synthetic 17 α-MT.…”
Section: Sex Determinationmentioning
confidence: 99%
“…All-male monosex culture is characterized by greater uniformity in growth, size and body weight, better flesh quality, more rapid growth and the lack of spawning. (5) Androgens, such as 17 α-methyl testosterone (MT), and carp testis (natural androgen), are widely used in this respect (6) as well as trenbolone or nonsteroidal aromatase inhibitors, such as fadrozole, which Introduction In current days most of Tilapia Nilotica (Oreochromis Nilotica) in Egyptian market comes from Monosex farming by using 17 α-Methyltestosterone (MT) sometimes misuse of this hormone cause harmful effect on a human who consumed fish containing MT hormone residues as it cause problems in puberty for girls and boys, liver tumors, carcinoma and increases embryo mortality.…”
Section: Introductionmentioning
confidence: 99%